Balzac hagiographe : Comédie humaine ou Légende dorée ? - Anne-Marie Baron (Les Dossiers du GRIHL)
The Human Comedy, competing in it with the hagiographic texts, seems to produce more examples than characters. Inspired by the Biblical or Christian figures, the heroes may suffer death and passion, leaving their sphere to rise until that of the “Speciality”. As Swedenborg writes: “The earth is the breading-ground for the sky”. Filled with martyrs and saints, this so-called realistic work is similar to a Bible of the 19th century or to the Voragine’s Golden Legend, the characters of which, bigger than nature, aim more than life, at immortality.